Vilnius as a Center of the Jewish Bund - Arūnas Vyšniauskas (Lietuvos Istorijos Studijos)
The article deals with the role of the Jewish Social Democrats of Vilnius in the process of the consolidation of the Russian Social Democratic movement. In the autumn of 1897, the General Jewish Workers' Union in Russia and Poland was established in Vilnius. Earlier, in the summer of that year, an important agreement was concluded in Switzerland between A. Kremer, the leader of the Jewish Social Democrats of Vilnius, and G. Plekhanov's Group. A. Kremer received written authorizations to convene a constituent congress of the Russian Social Democrats. It was decided at the 1st Congress of the Russian Social Democratic Workers' Party, which took place in Minsk (about 200 km away from Vilnius) in the spring of 1898, that the Jewish Bund was an incorporated part of the RSDWP. Five of the 9 participants in the 1st Congress of the RSDWP were Jews, with 3 representatives among them of the Bund from Vilnius.